An insight into the Islamic Manufacturing Practices (IMP) / Sharifah Fadylawaty Syed Abdullah ... [et al.] - Daud, Mohd Zaid; Jaapar, Nurzahidah; Ahmad, Thuraya (2017)
Indeed, al-Quran and al-Hadith have guided Muslims to steadfastly differentiate between halal and haram in worldly life. In terms of providing a top-notch halal goods and services, a company's practice should abide by Islamic values which cover the fundamental aspects of manufacturing, nurturing subordinates, safeguarding environment and managing financial issues. In fact, as a Muslim, opting for Halalan Toyyiba is part of worship to get pleasure from Allah and simultaneously nourishing his body and soul out from the goodness of permissible and pure products. In an attempt to identify an idea invented to gain a peek level of halal namely the Islamic Manufacturing Practices (IMP), a qualitative method is adopted by combining between semi-structured interview with the pioneer of IMP, site observations and library research in order to obtain holistic data on the matter. At the end, this paper finds that the occurrence of IMP significantly has a positive effect on the patronage behaviour of Muslim consumers. It is hope that, IMP has a deserving potential to pervade in halal Industry as a fraction of Good Manufacturing Practices (GMP) in current industry. In accordance with the finding, this paper suggests some improvements to the IMP practice in order to support economic growth for Muslims in particular, and as well as for Malaysia as a whole.